0.7(6x+9)=3.4-(x-3)

Simple and best practice solution for 0.7(6x+9)=3.4-(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.7(6x+9)=3.4-(x-3) equation:


Simplifying
0.7(6x + 9) = 3.4 + -1(x + -3)

Reorder the terms:
0.7(9 + 6x) = 3.4 + -1(x + -3)
(9 * 0.7 + 6x * 0.7) = 3.4 + -1(x + -3)
(6.3 + 4.2x) = 3.4 + -1(x + -3)

Reorder the terms:
6.3 + 4.2x = 3.4 + -1(-3 + x)
6.3 + 4.2x = 3.4 + (-3 * -1 + x * -1)
6.3 + 4.2x = 3.4 + (3 + -1x)

Combine like terms: 3.4 + 3 = 6.4
6.3 + 4.2x = 6.4 + -1x

Solving
6.3 + 4.2x = 6.4 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
6.3 + 4.2x + x = 6.4 + -1x + x

Combine like terms: 4.2x + x = 5.2x
6.3 + 5.2x = 6.4 + -1x + x

Combine like terms: -1x + x = 0
6.3 + 5.2x = 6.4 + 0
6.3 + 5.2x = 6.4

Add '-6.3' to each side of the equation.
6.3 + -6.3 + 5.2x = 6.4 + -6.3

Combine like terms: 6.3 + -6.3 = 0.0
0.0 + 5.2x = 6.4 + -6.3
5.2x = 6.4 + -6.3

Combine like terms: 6.4 + -6.3 = 0.1
5.2x = 0.1

Divide each side by '5.2'.
x = 0.01923076923

Simplifying
x = 0.01923076923

See similar equations:

| W/2.5=0.7 | | 2.33x+10+5.66x-9.5=12.5 | | 4x=8x+12x-16y | | M^2*m-30=0 | | 17(t-6)+4t=7(3t+4)-9 | | 2k^2-k-36= | | a/25=25 | | -5+8+-13= | | 2-4x=50 | | 0=x^4-29x^2-252 | | 2x-8+x=21 | | 2^(1/x)=0 | | 2^(1/x) | | 2/3x-2/3-2/5x+3/5-1 | | 2/x+3=5/2x+13/4 | | 7+3t-5=7t+10-3t | | 5+8+-13= | | 1.5x=15.17 | | 180=(x+3)+(2x-61) | | x-4.72=5.28 | | 7(t-4)+8t=5(3t+3)-11 | | 27-55= | | 3n^4-33n^2+30= | | 9-6x=63 | | 6/5y=8 | | 4x^2-12x-40= | | 2b-3.4/06=-29 | | 5x^2-22x+8= | | -2(3s-3)-6=-2(5s+10)-3 | | 17-29x=4(-13-5x) | | 11/5y=8 | | 9r=4(r-10) |

Equations solver categories